Susceptibility of Tiger Shrimp (Panaeus monodon) against Vibrio harveyi on various Molt Stage and Osmolarity - Gina Saptiani; Catur A Pebrianto; Agustina Agustina; Esti H Hardi (Jurnal Perikanan Universitas Gadjah Mada, 2016)
Vibrio harveyi causes disease of tiger shrimp (Penaeus monodon) aquaculture in East Kalimantan. This research aimed to investigate the susceptibility of tiger shrimp on various molt stage and osmolarity, and determine the salinity (osmolarity) of water that can reduce the risk of V. harveyi attack. Shrimp age of 1.5 months was maintained in 4 aquariums with salinity 29.72 ‰, 26.07 ‰, 22.35 ‰ and 17.79 ‰, then challenged with V. harveyi. After 7 and 14 days, osmolarity of haemolimph was observed with automatic osmometer and Digital Roebling Osmometer. The susceptibility of tiger shrimp to V. harveyi was evaluated based on clinical symptoms, pathological anatomy of shrimp and density of V. harveyi (TPC) in the hepatopancreas. Osmolarities of shrimp haemolymph at premolt, postmolt, and intermolt stage were 575.30-812.60; 534.00-788.80, and 566.20-795.60 mOsm/l H2O, respectively. The lowest bacterial content in the premolt stage was maintained at a salinity 22.35 ‰, and the highest one was obtained in postmolt stage at 29.72 ‰. The molting and postmolt stage were the most susceptible to V. harveyi attacks. The results suggested that the shrimp maintained at 22.35 ‰ salinity was less susceptible to V. harveyi.